Acoustic emission detection and position identification of transverse cracks in carbon fiber–reinforced plastic laminates by using a novel optical fiber ultrasonic sensing system. (May 2015) - Wu, Qi; Yu, Fengming; Okabe, Yoji; Saito, Kazuya; Kobayashi, Satoshi
Utilizing optical fiber technique to structural health monitoring of composite materials is attracting attention recently due to the inherent advantages in optical fiber sensor. However, acoustic emission signals with low energy and high frequency from transverse cracks in carbon fiber–reinforced plastic laminates are difficult to be detected by normal optical techniques. In this work, we present a phase-shifted fiber Bragg grating balanced sensing system to detect acoustic emission signals generated in a carbon fiber–reinforced plastic laminate in a three-point bending test. We demonstrated that the phase-shifted fiber Bragg grating balanced sensing system with a broad bandwidth and high sensitivity can detect high-frequency, low-energy acoustic emission signals caused by transverse cracks. In our experiments, the transverse cracks were identified very well through the detected acoustic emission signals. The relationship between the strain and the acoustic emission signals, and the typical waveforms of the acoustic emission signals were investigated. Furthermore, accurate position identification using acoustic emission detection by the phase-shifted fiber Bragg grating sensor was demonstrated. All the results obtained from the phase-shifted fiber Bragg grating sensor were compared to the results obtained from commercial lead–zirconate–titanate acoustic emission sensors. We found that the phase-shifted fiber Bragg grating balanced sensing system performance was comparable to the commercial lead–zirconate–titanate acoustic emission sensors.